Investigation on coagulation efficiency of polyaluminium silicate chloride (PASiC) coagulant - Gyawali, G; Rajbhandari (Nyachhyon), A (Scientific World, 2012)
Polyaluminium silicate chloride (PASiC) coagulant was synthesized by co-polymerization technique using aluminium salt and polysilicic acid at different OH/Al and Al/Si molar ratios. A synthetic turbid sample was used to investigate the coagulation efficiency of the prepared coagulant. After the coagulant dosing, flocculation time was set for 15 minutes followed by sedimentation for 20 minutes. High performance of coagulant was achieved at 2.5 molar ratio of OH/Al and 5 molar ratio of Al/Si at the optimal pH. The optimum pH range was found to be 7±0.5.The effective coagulant dose for the efficient removal of turbidity was set as 2.5 mg/L. As compared to conventional alum, PASiC has been found to be excellent inorganic polymeric coagulant for turbidity removal from water and residual aluminum was found to be minimal in comparison to conventional alum treatment. Hence, PASiC has proven the potentiality for the turbidity removal in water treatment over conventional alum. Scientific World, Vol. 10, No. 10, July 2012 p33-37 DOI: http://dx.doi.org/10.3126/sw.v10i10.6859